The Influence of Green Customers and Content Marketing on Gen Z’s Repurchase Intention for Skintific on TikTok Shop - Fifi Firdayanti; Lis Tatin Hernidatiatin (Mabsya: Jurnal Manajemen Bisnis Syariah, 2026)
Indonesia's cosmetics sector experienced intense competition in 2025. Despite a remarkable turnover surge, Skintific faced a paradoxical competitiveness decline, signaling weakening retention. This study addresses the research gap concerning post-purchase loyalty among Gen Z by analyzing how Green Customer psychology and Content Marketing drive Repurchase Intention within TikTok Shop. A quantitative, associative design was employed. Data were collected from 150 active Gen Z TikTok Shop users with at least two prior Skintific purchases. The proposed relationships were tested using PLS-SEM. Findings indicate the model explains 61.0% of repurchase intention variance (R² = 0.610). Partially, Green Customer behavior (β = 0.329; p < 0.05) and Content Marketing (β = 0.537; p < 0.05) each exert positive, significant effects. Notably, Content Marketing shows larger practical impact (f² = 0.467) than Green Customers (f² = 0.175). These results confirm that Gen Z's loyalty hinges not only on product sustainability but significantly on interactive, credible digital narratives. Practically, brand management should integrate eco-friendly education into creative content strategies to reduce churn and maintain sustained competitiveness amid dynamic digital trends.